Morphological Variation of Suprascapular Notch in Population of Eastern India and its Clinical Significance - BANANI KUNDU; PALLAB KUMAR SAHA; BILESWAR MISTRY; TANUSHREE ROY (International Journal of Anatomy Radiology and Surgery, 2021)
Introduction: Suprascapular notch is present at the lateral part of the superior border of scapula which is bridged by superior transverse scapular ligament. The suprascapular nerve runs below the ligament and the transverse scapular vessels over it. The ligament sometimes becomes ossified and impinges the underlying nerve which causes paralysis of both supraspinatus and infraspinatus muscles. Aim: To study the morphological variation of suprascapular notches in dry human scapulae. Materials and Methods: This observational cross-sectional study was carried out on 102 adult dry human scapulae (62 right, 40 left) collected from the 1st year MBBS students of different Medical colleges of West Bengal from August 2020 to March 2021. The shapes of suprascapular notch, presence of ossified ligaments were observed. Superior Transverse Diameter (STD), Middle Transverse Diameter (MTD), Maximum Depth (MD) of the suprascapular notch, distance from the deepest point of suprascapular notch to supraglenoid tubercle and distance between the spinoglenoid notch to the posterior rim of glenoid cavity were measured and statistically analysed. Classification of the suprascapular notch was done based on Rengachary classification. Results: Type III notch was most common (n=52). One scapula had small U-shaped notch with lateral part of the ligament ossified and another had U-shaped notch with both medial and lateral part of the ligament ossified but they failed to join. In Type I and Type VI there were no such diameters like STD or MTD but for other types STD was more than MTD. The distance between suprascapular notch and supraglenoid tubercle was variabletype VI had minimum and type I had the maximum distance. The distance between the medial wall of the spinoglenoid notch and the posterior rim of glenoid cavity was least in type I and highest in type III. Conclusion: This study showed that type III was the most common suprascapular notch. The present study also compared the findings with other previous studies and found that percentage of presence of suprascapular foramen in this eastern Indian population was higher than southern Indian population.